IMPROVING THE PROFESSIONAL COMPETENCES OF FUTURE ENGINEERS IN A DIGITAL EDUCATIONAL ENVIRONMENT - Kuziyev Botir Nomozovich; Salimov Esanjon Xusen o’g’li (The Conference Hub, 2025)
This article defines the tasks of forming and improving the professional competencies of future engineers in a digital educational environment in Uzbekistan and improving the professional competencies of engineers in a digital educational environment in technical higher educational institutions.
Keywords: digital education, professional competence, competence, modular training.